(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the interrelationship between the Sustainable Development Goals (SDGs) and education. Education is seen as an important tool in ensuring sustainable development in the social, economic and environmental spheres. It also discusses the contribution of the education system to sustainable development, its role in educating the younger generation as conscious citizens, and the importance of education in solving global problems.